Optimization and Kinetics of Terbium Leaching from Lapindo Mud using Sulfuric Acid as the Leaching Agent - Supriadi, Harry; Suyanti, Suyanti; Astuti, Widi; Handini, Tri; Sujoto, Vincent Sutresno Hadi; Prameswara, Gyan (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
This study investigated the impact of solid/liquid ratio, solvent concentration, temperature, and leaching time on the recovery of rare earth elements (REEs), particularly terbium, from Lapindo mud using sulfuric acid as a leaching agent. The objective was to optimize the leaching conditions and identify the most appropriate kinetic model for describing the extraction process. Leaching experiments were conducted under various solid/liquid ratios, sulfuric acid concentrations, temperatures, and time. The findings revealed that the maximum terbium recovery of 94.51% was achieved at a solid/liquid ratio of 0.5, and 18 M sulfuric acid was used as the leaching agent for the extraction process at 200 °C for 30 minutes. Kinetic analysis proved that the Zhuravlev-Leshokin-Templeman (ZLT) model best described the leaching process. The calculated reaction's apparent activation energy (Ea) was 27.96 kJ/mol, indicating that a combination of chemical reactions and diffusion mechanisms controls the leaching process. These insights are crucial for optimizing the extraction of terbium and other REEs from Lapindo mud, offering significant potential for industrial applications in recovering valuable materials from waste sources. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).